Dual malignancy: a rare presentation of synchronous periampullary carcinoma with renal cell carcinoma - Kumar, Lovekesh; Sundar, Shyam; Vindal, Anubhav; Lal, Pawanindra (International Surgery Journal, 2020)
The occurrence of synchronous pancreatic cancer and other primary cancer is not frequent and reaches about 5.6% as reported in autoptic studies. Double resections of the pancreas with another organ due to synchronous malignancies have been published only in quite sporadic sets of cases or individual case reports. We present a case report of a 40 years lady who presented with intermittent pain, fever and jaundice for 15 days. Examination revealed a palpable gall bladder, firm in consistency and tender to touch. She was admitted with a provisional diagnosis of cholangitis and started on intravenous antibiotics. Patient’s clinical condition improved and she was planned for a CECT and MRCP which revealed an heterogenously enhancing mass lesion in upper pole of left kidney, s/o of renal cell carcinoma (RCC) and an enhancing lesion in periampullary region s/o periampullary carcinoma with no evidence of free fluid or metastasis. ERCP guided biopsy revealed moderately differentiated adenocarcinoma and USG guided renal biopsy revealed clear cell carcinoma. Whipple’s procedure with left nephrectomy was performed. Intra operative findings revealed post-operative course and hospital stay was uneventful. Biopsy revealed poorly differentiated pancreaticobiliary adenocarcinoma with no lympho vascular or lymph nodal invasion (pT3aN0) and left sided clear cell renal carcinoma with no lympho vascular invasion (pT1N0). Synchronous malignancy of pancreas and kidney is a very rare presentation. Literature describes presence of RCC with periampullary metastasis and patients presenting with RCC post whipple’s procedure but only a handful of case reports describe presence of dual malignancy as reported above.